Use of information technologies in the procedure of registration in the Real Estate Cadastre - Živković Miloš (Zbornik Radova Pravnog Fakulteta u Nišu, 2019)
The 2018 Act on the Registration Procedure with the Real Estate Cadastre and Utilities Cadastre has brought many novelties in the Serbian land registration law, the most important being the ex officio registration of rights in the real estate cadastre. This significant novelty has been primarily made possible by technological innovations and networking of various state bodies and holders of public authority. The paper contains an overview of the overall registration procedure as set forth in the new legislation and, especially, the role of information technologies and electronic communication in the registration procedure. Serbia is currently in a transition period, moving away from the formerly existing "paper-based" registration procedure, through the currently applicable registration procedure based on "digitalized" analogue documents, and moving towards the desired registration procedure that shall be fully based upon digital, electronic documents. The paper emphasizes the challenges that may be encountered by lawyers in the process of using information technologies in the procedure of registration in the real estate cadastre, and outlines the trends of future development in this area.